Can Sexual Appeal, Beauty, or Virtue Increase the Opportunity for a Woman to Be Selected as a Spouse? The Mediating Role of Human Uniqueness - Lai, Ji; Ding, Daoqun; Chen, Xinling; Li, Shenglan (Frontiers in Psychology, 2021)
High mating value is believed to correspond with high mating opportunities. On that premise, this study explores three cues that are linked to women of high long-term mating value, namely a “beautiful” facial appearance, “sexually attractive” body shape, and “virtuous” behavior. With exclusive attention focused on the above cues, this study examines what kind of human attributes would make a contribution to women’s mating opportunities. The results reveal that both ‘beautiful’ women and ‘virtuous’ women were assessed (in this study) as having greater mating opportunities than ‘sexually attractive’ women. In regard to the human attributes, only the ‘beautiful’ woman was assessed as having high levels of human uniqueness and human nature. Meanwhile, ‘virtuous’ women were assessed as having higher levels of human uniqueness but lower levels of human nature. In contrast, ‘sexually attractive’ women were assessed as having lower levels of human uniqueness but higher levels of human nature. In addition, the results of a mediation analysis show that the trait of human uniqueness, and not human nature, was the mediator between the three types of women and women’s mating opportunities. This finding means that when women have higher levels of human uniqueness, they can acquire more mating opportunities. These findings contribute an improved understanding to why and how ‘beauty’ or ‘virtue’ increases the opportunity for woman to be selected as a spouse.